Synthesis and Characterization of Novel Integral Asymmetric Monophasic Cellulose–Acetate/Silica/Titania and Cellulose–Acetate/Titania Membranes - Inês Peixoto; Mónica Faria; M. Clara Gonçalves (Membranes, 2020)
Two series of novel integral asymmetric monophasic hybrid membranes, cellulose acetate/silica/titania (CA/SiO2/TiO2—series 1) and cellulose acetate/titania (CA/TiO2—series 2), were developed by the coupling of sol-gel technology and a modified version of the phase inversion technique. SEM micrographs confirmed the integral asymmetric structure of all membranes. ATR-FTIR and ICP-OES results showed that, for the membranes in series 1, TiO2 is covalently bound to SiO2, which, in turn, is covalently bound to CA, while for the membranes in series 2, TiO2 is directly and covalently bound to the CA matrix. Permeation experiments revealed that the permeation performance of the membranes in series 1 is unaffected by the introduction of TiO2. In contrast, the introduction of TiO2 in the series 2 membranes increased the hydraulic permeability by a factor of at least 2 when compared to the pristine CA membrane and that incremental additions of TiO2 further increased the Lp.